Applying balanced scorecard to Hellenic navy’s education and training: an initial approach - Stavrakakis, Panagiotis; Roka, Vasiliki; Malliarou, Maria; Sarafis, Pavlos (My University, 2010)
Like organizations striving for growth, Hellenic Navy is facing rising pressure to increase the value added by its services. To meet this challenge in an era of scarcity of resources Hellenic Navy’s education and training will need to undergo fundamental changes in the way they operate and continuously seek ways to create future value. This paper explores and discusses the potential applicability of Balanced Scorecard in Hellenic Navy’s education and training in order to stimulate and sustain continuous improvement. Favorable results were reported in the for-profit and government organizations supporting the aforementioned applicability.
Keywords: Hellenic navy’s education and training; Scorecard to Hellenic navy’s education and training; Balanced scorecard